Shovel Shaped Incisors: A Non-Metric Dental Trait in Local Population of Punjab, Pakistan: Non-Metric Dental Traits - Bano, Shaher; Nawaz, Rai Sadaf; Zafar, Roshan; Hassan, Ghazala; Javed, Mariyah; Yasen, Ariba (Pakistan Journal of Health Sciences, 2025)
Maxillary Incisors being the anterior teeth hold great importance for function and esthetics. Different morphological traits can affect the shape of incisors. Shoveling is a non-metric morphological trait predominantly seen in maxillary incisors and is characterized by prominent mesial and distal ridges enclosing a central fossa on the lingual surface of incisors. Objective: To determine the frequency of shovel shaped Incisors and its distribution according to gender in a local population of Punjab, Pakistan. Methods: The study was a cross-sectional study carried out on 176 students of age between 17-23 years. Probability, stratified random sampling technique was employed and the study was conducted from March, 2023 to November, 2023. The participants taken for the study were carefully examined clinically to diagnose the presence or absence of this trait. Results: Out of total population of 176, only 55 (31.2%) individuals were positive for shoveling trait. Among the positive individuals, no gender predilection of this trait was observed. Conclusion: Non-metric dental traits can be assessed to identify ethnic groups, forensic odontology and inform clinical management in various dental procedures.